2004
DOI: 10.1093/carcin/bgh158
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-derived and host-derived nitric oxide differentially regulate breast carcinoma metastasis to the lungs

Abstract: To study the role of nitric oxide (NO) in lung metastasis of breast carcinoma, we isolated two cell clones (H and J) from the parental EMT-6 murine breast carcinoma cell line, based on their differential NO production. In vitro, EMT-6 J cells, but not EMT-6H cells, constitutively expressed inducible NO synthase (NOS II) and secreted high levels of NO. IL-1beta increased NO production in both clones, and TNF-alpha had a synergistic effect on IL-1beta-induced NO production, but NO production by EMT-6 J cells was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Cytotoxicity-The toxicity of the supernatants from wild type or PLTP Ϫ/Ϫ splenocytes treated with the high LPS dose was assessed by determining their impact on the ability of EMT-6J cells to adhere to plastic according to the general procedure previously described (47,48). Results were expressed as a percentage of adherent cells, 100% adhesion corresponding to the control value obtained in the absence of LPS.…”
Section: Ex Vivo Response Of Mouse Splenocytes To Lps-splenocytesmentioning
confidence: 99%
“…Cytotoxicity-The toxicity of the supernatants from wild type or PLTP Ϫ/Ϫ splenocytes treated with the high LPS dose was assessed by determining their impact on the ability of EMT-6J cells to adhere to plastic according to the general procedure previously described (47,48). Results were expressed as a percentage of adherent cells, 100% adhesion corresponding to the control value obtained in the absence of LPS.…”
Section: Ex Vivo Response Of Mouse Splenocytes To Lps-splenocytesmentioning
confidence: 99%
“…Mammary adenocarcinoma EMT6 cells are a widely used model to study different aspects of growth control in cancer (21)(22)(23)(24)(25). A broad variety of chemical compounds (23), growth factor inhibitors, and other biomolecules, including cytokines either alone or in combination with endocrine modulation (22), have been studied using in vitro and in vivo settings in this model.…”
Section: Il-22-mediated Tumor Growth Reduction Correlates With Inhibimentioning
confidence: 99%
“…Previously, along with Ridder et al, we reported that this cytokine could be produced by immune cells when they were activated by OM-174. 22,34 Nunez et al 33 evoked such a scenario. They demonstrated that a TLR-activated melanoma produces IFNb, which contributes positively to the antitumor immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Murine mammary EMT-6H cells were obtained after cloning of the EMT-6 cell line 34 and the mammary NT2 cancer cell line was purchased from the ATCC. Balb/c mice, Fvb mice, IFNg, TLR4, and NOS II knockout mice were purchased from Charles River Laboratory International.…”
Section: Cells Animals and Treatmentmentioning
confidence: 99%